Sustainable City Planning Concepts and Practices in Emerging Economies: A Systematic Review - Chrisna T. Permana; Budi Harsanto (The Journal of Indonesia Sustainable Development Planning, 2020)
The purpose of this paper is to explore sustainable city planning concepts and practices in emerging economies. Using a systematic review, peer-reviewed articles in an academic database were systematically searched and reviewed. The process included selecting appropriate keywords to assist in screening relevant articles, allowing more comprehensive and integrated findings of the concepts and practices of sustainable city planning in emerging economies, assisted by the NVivo 12 qualitative software package and Microsoft Excel. This paper also developed a framework comprised of key elements to measure the sustainability of city planning. The findings showed that, by reviewing more than 30 peer- reviewed articles, it was understood that Western sustainable city planning concepts have been directly adopted into the policy agendas of emerging countries without significant changes. However, such concepts were interpreted into a number of different practices dealing with the local socio-cultural and political characteristics of the adopting countries. Lastly, during the systematic review, this paper offers a comprehensive evaluation of the overall mapping of literature in the framework of sustainable city planning in emerging countries, indicating a number of areas that have been explored by existing studies as well as certain areas that are still lacking and could be potentially explored by future studies.